Development and Application of a Program for Reinforcing Global Health Competencies in University Nursing Students - Won Ju Hwang; Hyun Hee Jo (Frontiers Media S.A., 2020)
Purpose: With globalization, the importance of global health is being stressed. Although nurses are indispensable healthcare professionals, programs to develop nurses with global health competencies and relevant studies are rare. Accordingly, this study was designed to develop a program to increase global health competencies and global leadership in nursing students and test its effect.Methods: A single group pre- and post-test study design was used. A 13-weeks program was developed and implemented with 204 students. Data were analyzed using paired t-test. The program to promote global health competencies was designed to improve nursing students' knowledge of global health, global leadership, global health competencies, critical thinking ability, and student-student partnership.Results: Global health competencies (t = −19.96, p < 0.001), self-assessed global leadership (t = −7.67, p < 0.001), and critical thinking ability (t = −7.67, p < 0.001) all significantly increased.Discussion: The study findings of increased global health competencies and global leadership in nursing students after participation in the program indicated ways in which global health competencies of nurses need to be developed. Therefore, the following aspects should be considered. First, nursing educators should understand the need and importance of global health education and accordingly, current nursing curriculums should be revised to include courses about global health. A systematic course of studies about global health should be developed and implemented based on discussions among experts and researchers. Second, as future health care professionals, nursing students should take an interest in global health problems and recognize various issues that need to be solved beyond borders between countries. To develop global health competencies, various efforts and systematic curriculum revisions are necessary.